Words of experience: translating Islam with Carl W. Ernst - Fuerst, Ilyse R. Morgenstein; Wheeler, Brannon M.; Ernst, Carl W. (Comparative islamic studies, 2021)
"This volume features contributions from long-standing colleagues, scholars whose own work has built on Ernst's contributions, and former students. It looks at themes in Islamic studies which Ernst has addressed and expands on his major contributions"--